PEMODELAN KETERKAITAN ANTAR FAKTOR KENDALA PENERAPAN TEKNOLOGI TERBATAS (PILOT PROJECT) BIDANG JALAN MELALUI PENYEDIA JASA - Kiki Mohammad Iqbal; Anton Soekiman (Rekayasa Sipil, 2021)
The Institute of Road Engineering (IRE) is an institute dealing with research and development in the field of roads. Application of Pilot Project through service providers is an implementation of transfer of intellectual property technology with high risk. Using Interpretive Structural Modeling method and MICMAC analysis to identify, classify the contextual relationships the constraints factor of Pilot Project. In this study produce 23 constraint factors. The low quality of scheduling project implementation is the most influenced factor (Dependence) while the problem of the financial ability of the contractor to finance the work and give the project to the lowest bid is the key factor the most affecting (Driver Power) hierarchically. This analysis supports decision making make priorities for problem solving.